Positioning Strategy of PT. Guten. Inc: SWOT Analysis Approach - Fitriani Latief; Asniwati; Yafi Nur Akram (Jurnal Manajemen Bisnis, 2021)
The current study aims to (a) find out the quadrant position of PT Guten Inc's based on the results of SWOT analysis (b) find out the proper positioning strategy to be applied by PT Guten Inc based on the results of SWOT analysis. The research was conducted by using a quantitative approach with data collection techniques are through direct observation, interviews, questionnaires and literature studies. The analysis was based on internal and external environmental factors which influences decision making of corporate strategy. Data processing applied IFAS & EFAS matrix and SWOT matrix. Result of IFAS matrix was 3.29 and EFAS matrix was 3.19, which means that PT Guten.Inc is positioned at cell II in SWOT matrix so that strategy can be done is aggressive strategy. Results of SWOT matrix analysis shows that it was in quadrant II with SO (Stregth-Opprtunity) strategy of the aggressive strategy that can be applied which means that PT Guten Inc can take advantage of opportunities with maximum strength.